Communicative basis of teachers’ training in multicultural conditions - Vinnikova, Мarina N.; Venidiktova, Elena V.; Venidiktova, Elena V.; Khairullina, Elmira Robertovna; Nasretdinova, Aziza Salavatovna (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The main aim of the study is to investigate the formation of the professional competence of a foreign language teacher. This is due to the modern socio-cultural conditions, new educational standards and the ever-increasing requirements for the process of teaching foreign languages. Based on the results, it can be concluded that the professional competence of a foreign language teacher is a complex of various skills and abilities facilitating effective cooperation between the teacher and students in certain professional situations. The multifaceted consideration of the problem of the formation of a teacher’s professional. The authors see the solutions to these problems, the creation of a flexible and mobile system of advanced training and the search for new, more effective forms of interaction between educational institutions, methodological services, and professional associations of teachers for purposeful continuous pedagogical education of teachers of a foreign language.